Assessment of Immunological Response and Impacts on Fertility Following Intrauterine Vaccination Delivered to Swine in an Artificial Insemination Dose - Hamonic, Glenn; Pasternak, J. Alex; Ng, Siew Hon; Fourie, Kezia R.; Simko, Olena M.; Deluco, Brodie; Wilson, Heather L. (Frontiers in Immunology, 2020)
To protect the health of sows and gilts, significant investments are directed towards the development of vaccines against infectious agents that impact reproduction. We developed an intrauterine vaccine that can be delivered with semen during artificial insemination to induce mucosal immunity in the reproductive tract. An in vitro culture of uterine epithelial cells was used to select an adjuvant combination capable of recruiting antigen-presenting cells into the uterus. Adjuvant polyinosinic:polycytidylic acid (poly I:C), alone or in combination, induced expression of interferon gamma, tumour necrosis factor alpha, and select chemokines. A combination adjuvant consisting of poly I:C, host defence peptide and polyphosphazene (Triple Adjuvant; TriAdj), which previously was shown to induce robust mucosal and systemic humoral immunity when administered to the uterus in rabbits, was combined with boar semen to evaluate changes in localized gene expression and cellular recruitment, in vivo. Sows bred with semen plus TriAdj had decreased γδ T cells and monocytes in blood, however, no corresponding increase in the number of monocytes and macrophages was detected in the endometrium. Compared to sows bred with semen alone, sows bred with semen plus TriAdj showed increased CCL2 gene expression in the epithelial layer. These data suggest that the adjuvants may further augment a local immune response and, therefore, may be suitable for use in an intrauterine vaccine. When inactivated porcine parvovirus (PPV) formulated with the TriAdj was administered to the pig uterus during estrus along with semen, we observed induction of PPV antibodies in serum but only when the pigs were already primed with parenteral PPV vaccines. Recombinant protein vaccines and inactivated PPV vaccines administered to the pig uterus during breeding as a primary vaccine alone failed to induce significant humoral immunity. More trials need to be performed to clarify whether repeated intrauterine vaccination can trigger strong humoral immunity or whether the primary vaccine needs to be administered via a systemic route to promote a mucosal and systemic immune response.